Influence of glutamine on morphological and functional changes of liver in the presence of extrahepatic biliary obstruction in rats - Paiva Neto,Manoel Camelo de (2010)
PURPOSE: To study the influence of glutamine on functional and morphological changes of liver in the extrahepatic biliary obstruction through an experimental model in rats. METHODS: Seventy Wistar rats were divided into four groups: control (group C) fictitious operation, (group FO), submitted to laparotomy with handling of bile ducts, but without hepatic duct ligation, (group EBO) submitted to laparotomy and hepatic duct ligation, one of them submitted to supplementation with glutamine 2% (group G). The control group consisted of 6 animals. The animals from groups FO, EBO and G were divided into three groups consisting of 6 animals each, being sacrificed at 7, 14 and 21 days after operation, respectively. Blood samples were collected for biochemical analysis and a fragment of liver tissue was collected from the middle lobe for histological analysis. RESULTS: Both for biochemical analysis (BT, aspartate and alanine aminotransferase AST, ALT and alkaline phosphatase FAL) and for histopathological changes (fibrosis, portal inflammation, parenchymal inflammation, hepatocytic changes and duct proliferation), no statistical difference between groups submitted to extrahepatic biliary obstruction (EBO) with and without treatment with glutamine (G) was observed. CONCLUSION: Glutamine supplementation did not alter the prognosis of liver enzymes and histopathological changes in animals submitted to extrahepatic biliary obstruction.